Correlation between BCG Immunization Status and The Incidence of Tuberculosis among Children - Annisa Nisa; Ulfa Hamdanah; Anita Dwi Ariyani (Babali Nursing Research, 2020)
Introduction: A children tend to have a high risk on the tuberculosis (TB) infection. BCG immunization is well known as effective way to protect the children from the infection of TB bacteria. Therefore, the study aim was to investigate a correlation between BCG immunization status and the incidence of tuberculosis among children. Methods: A retrospective case-control study design was used. In total 34 children, whose aged between 1 to 12 years old and visited Wonorejo Primary Health Center between September, 12nd to 16th 2019 recruited as study participant. The Chi-square test was used in this study. Results: There was a significant correlation between BCG immunization status and the incidence of tuberculosis among children with P value = .008, < .05. Conclusion: Among five from six children who did not received the BCG immunization were suffered with TB bacteria infection.